Remembering with a friend or a stranger: comparing acquainted and unacquainted pairs in collaborative eyewitness interviews. Issue 10 (26th November 2019) - Vredeveldt, Annelies; van Deuren, Sjoukje; van Koppen, Peter J.
ABSTRACT: Previous findings show that collaborative interviews with pairs of eyewitnesses can result in more accurate testimony than individual interviews, and that partners remember more together if they acknowledge, repeat, rephrase and elaborate upon each other's contributions. In the present study, we investigated whether these findings differ for pairs of acquainted and unacquainted partners, respectively. Participants viewed a violent movie in the cinema and took part in three eyewitness interviews approximately five days later. The first and the last interview were always individual. The second interview was individual in the nominal condition ( N  = 22 pairs), collaborative with a known partner in the acquainted condition ( N  = 21 pairs), and collaborative with a stranger in the unacquainted condition ( N  = 20 pairs). We replicated benefits of collaborative eyewitness interviews, in terms of error pruning as well as delayed cross-cuing. However, we found no significant differences between acquainted and unacquainted pairs, neither in recall performance nor in retrieval strategies during the collaborative interview. Regardless of acquaintance, pairs who elaborated upon each other's contributions during the collaborative interview, remembered more together. The findings are evaluated within the theoretical framework of transactive memory. Practical implications for investigative interviewers are discussed.